2014
DOI: 10.21836/pem20140408
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of inflammatory markers in chronic respiratory disease of the horse – a review

Abstract: Summary: Over the last years local and systemic inflammatory markers of chronic pneumopathies have gained increasing interest in research, as the pathogenesis of Recurrent airway obstruction (RAO) and Inflammatory airway disease (IAD) remains not fully elucidated in several details. In human medicine, Asthma bronchiale and Chronic obstructive pulmonary disease (COPD) have been found to be influenced by systemic inflammatory processes and the other way around. Inflammation, coagulation and fibrinolysis as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
(152 reference statements)
1
1
0
Order By: Relevance
“…Compared to these controls, all horses of the presented study showed increased levels of MMP 2, 8 and 9 prior to therapy. Increased TIMP levels have also been found in humans suffering from asthma [23, 24, 28, 29] and the same was found for equine RAO in this study and previous [26, 27]. This may allow the suspicion that fibrosis formation as a long-term consequence of human asthma and equine RAO may be the ultimate result of continuous activation of tissue repair mechanisms or over-repair processes [30].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Compared to these controls, all horses of the presented study showed increased levels of MMP 2, 8 and 9 prior to therapy. Increased TIMP levels have also been found in humans suffering from asthma [23, 24, 28, 29] and the same was found for equine RAO in this study and previous [26, 27]. This may allow the suspicion that fibrosis formation as a long-term consequence of human asthma and equine RAO may be the ultimate result of continuous activation of tissue repair mechanisms or over-repair processes [30].…”
Section: Discussionsupporting
confidence: 86%
“…Elastinolytic and collagenolytic activity was found in several studies on human asthma, in particular increased levels of MMP-9 [22, 23], but also MMP-2 [24, 25]. Former studies of our group showed that this is also true for several equine pneumopathies including RAO, inflammatory airway disease (IAD) and chronic interstitial pneumopathy compared to healthy controls [26, 27]. Compared to these controls, all horses of the presented study showed increased levels of MMP 2, 8 and 9 prior to therapy.…”
Section: Discussionmentioning
confidence: 95%